The The Role of Community Initiatives in the Implementation of Zero-Waste Policy in Kendal Regency: Case Study of KerDUS Community - Hidayati, Nanik; Rizqiani, Septika; Sunandar, Muhamad Aris (Sekolah Tinggi Pertanahan Nasional, 2025)
The waste problem increasingly threatens life. The biosphere encompasses both land and water bodies. Burned waste causes air pollution and produces greenhouse gases that contribute to global warming. Various methods have been implemented, including recycling, but only 20% of waste is successfully recycled. This This study investigates efforts to reduce waste by adopting a zero-waste lifestyle in Kendal Regency, Indonesia, with the participation of the KerDUS Community. The research employs qualitative methods such as interviews, documentation, participatory observation, and literature review. The results show that the education and training conducted by the KerDUS Community have successfully increased public awareness of the importance of waste management. This article also examines the environmental policies needed to support the implementation of a zero-waste lifestyle, including regulations, incentives, and the development of recycling infrastructure. We also discuss strategies to increase awareness and community participation through continuous education, environmental campaigns, and collaboration between the government, communities, and the private sector. With the right policies, it is hoped that the zero-waste lifestyle can be more widely and effectively implemented to reduce waste generation and its negative impacts on the environment in Kendal Regency.